THE INFLUENCE OF INFLATION AND UNEMPLOYMENT ON ECONOMIC GROWTH IN INDONESIA PERIOD 2003-2022 - Rizky Amelia Zahra (Jurnal Ekonomi, 2023)
The purpose of this study was to determine the effect of inflation and unemployment on economic growth in Indonesia for the 2003-2022 period. This research is a quantitative research. In this study, the type of data used is multiple linear regression analysis with secondary data. Data collection through the Central Bureau of Statistics (BPS) with the website https://www.bps.go.id. Data analysis in this study uses the classical assumption test. Data processing uses the SPSS application program version 26. Based on the test results, there is a positive and significant influence between inflation and unemployment on economic growth in Indonesia in the period studied.